2009
DOI: 10.1113/jphysiol.2008.163691
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide (NO) does not contribute to the generation or action of adenosine during exercise hyperaemia in rat hindlimb

Abstract: Exercise hyperaemia is partly mediated by adenosine A 2A -receptors. Adenosine can evoke nitric oxide (NO) release via endothelial A 2A -receptors, but the role for NO in exercise hyperaemia is controversial. We have investigated the contribution of NO to hyperaemia evoked by isometric twitch contractions in its own right and in interaction with adenosine. In three groups of anaesthetized rats the effect of A 2A -receptor inhibition with ZM241385 on femoral vascular conductance (FVC) and hindlimb O 2 consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…In contrast, other studies have shown that NOS inhibition does not affect the increase of blood flow evoked in forearm or leg exercise in humans, rats, and rabbits [2730]. Also, Ray and Marshall [31] reported that during exercise, adenosine originates from skeletal muscle fibers independently of NO and acts directly on adenosine A 2A AR on the vascular smooth muscle to evoke vasodilatation. As far as the absence of eNOS in eNOS −/− mice, the coronary flow is also not altered [14], and it has been suggested that either up-regulation of different NOS isoform (s) or enzyme(s) that produce other vasodilators as an alternate mechanism proposed for the unaltered coronary flow in eNOS null mice [14].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have shown that NOS inhibition does not affect the increase of blood flow evoked in forearm or leg exercise in humans, rats, and rabbits [2730]. Also, Ray and Marshall [31] reported that during exercise, adenosine originates from skeletal muscle fibers independently of NO and acts directly on adenosine A 2A AR on the vascular smooth muscle to evoke vasodilatation. As far as the absence of eNOS in eNOS −/− mice, the coronary flow is also not altered [14], and it has been suggested that either up-regulation of different NOS isoform (s) or enzyme(s) that produce other vasodilators as an alternate mechanism proposed for the unaltered coronary flow in eNOS null mice [14].…”
Section: Discussionmentioning
confidence: 99%
“…28 This suggestion was based on the observation that adenosine made a substantial contribution to muscle vasodilation when NOS was inhibited. Because the vasodilatory effect of adenosine depends not only on NO formation but also on prostanoid formation, 3 the vasodilatory effect of adenosine during NOS blockade in the study by Ray and Marshall 28 may well reflect PGI 2 -mediated vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…In A , n = 10; in B and C , n = 12 rats. Modified from Ray & Marshall (2009 a , b ). In D , the effects on FVC of breathing air or 40% O 2 without or with 8‐SPT are compared.…”
mentioning
confidence: 99%
“…1). Furthermore, when an NO donor or cell‐permeant cGMP was infused after NOS inhibition so as to restore the tonic dilator effect of NO and cGMP levels in the vascular smooth muscle, exercise hyperaemia was fully restored and A 2A receptor blockade had the same effect as before NOS inhibition (Ray & Marshall, 2009 b ; Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation